Applying formative evaluation in the mentoring of student intern nurses in an emergency department - Zhang, Yan-ru; Hu, Rong-fang; Liang, Tian-yu; Chen, Jian-bang; Wei, Yang; Xing, Yan-hong; Fang, Yan (Frontiers in Public Health, 2022)
Objective To explore the effectiveness of formative evaluation in the mentoring of student nursing interns in an emergency department. Methods A total of 144 intern nursing students in the emergency department of a tertiary care hospital in Fuzhou were selected as the study subjects from July 2020 to February 2021. Adopting quasi-experimental studies methods, the students were divided into the experiment group (n = 74) and the control group (n = 70), based on their practicing rotation times. Formative evaluation methods such as in-person interviews, clinical scenario simulations, and clinical operation skills exams were conducted in the experiment group, while traditional summative evaluation methods were adopted for the control group. At the end of the intern period, a unified examination paper on professional knowledge concerning the emergency department, a cardiopulmonary resuscitation skill assessment, and a self-rating scale of self-directed learning was employed to evaluate professional theory performance, clinical practice ability, self-directed learning ability, and academic satisfaction among the nursing students, respectively. Results The professional theoretical performance, clinical practice ability assessment scores, academic satisfaction, and self-directed learning abilities of the nursing students were significantly higher in the experiment group compared with the control group (P < 0.05). Conclusion The application of formative evaluation during the mentoring of student intern nurses in an emergency department improved their professional theoretical performance, clinical practice skills, academic satisfaction, and self-directed learning abilities.